Observations on phagocytosis of urate crystals by polymorphonuclear leucocytes. - Rajan, K T (1975)
The sequence of events that may initiate the inflammatory reaction in acute gout has been investigated with specific reference to phagocytosis of urate crystals by polymorphonuclear leucocytes and the results have shown (1) that neutrophil leucocytes avidly ingest microcrystals of sodium monourate, (2) that this causes the rapid degranulation and disintegration of the leucocytes, (3) that fresh leucocytes ingest the debris and crystals liberated by the dead cells, and in their turn degranulate and die, thus possibly establishing a vicious circle in the system.